Picking Up Opportunities, Organizing Hopes: Socialization of Smart Program to Choose the Future for Penabur High School Students Thanks to Tuapeijat - Asnur, Lise; Abdurrahman, Nabil; Navisa, Qavka; Juwita, Bella; Anggraini, Marshella; Tasiripoula, Patrisius (Journal of English Language and Education, 2025)
Adolescents in island regions still face limited access to information regarding higher education, scholarship opportunities, and the risks of negative behaviors that may close their future opportunities. This condition underlies the implementation of the Cerdas Memilih Masa Depan program by Universitas Negeri Padang students through the Community Service Program (KKN) at SMA Penabur Berkat, Tuapeijat, Sipora Utara, Mentawai. The activity was conducted on July 6, 2025, involving 25 twelfth-grade students. The methods used were interactive lectures, group discussions, a simple interest–talent simulation, and question–answer sessions supported by PowerPoint presentations and concise modules. The results showed an increase in students’ understanding of strategies for choosing majors and universities, knowledge of scholarship opportunities, and awareness of avoiding risky behaviors such as early marriage, drugs, and online gambling. This program demonstrates that participatory-based socialization is effective in increasing the motivation of Mentawai adolescents and has the potential to be developed as a sustainable strategy in preparing a more visionary young generation.